RNA Relocation and Persistence of Nucleolus-Like Bodies at Mitosis in Benzo[a]Pyrene-Transformed Human Breast Epithelial Cells after Microcell-Mediated Transfer of Chromosomes 11 and 17 - Maria Luiza S. Mello; Mohamed H. Lareef; Benedicto C. Vidal; Jose Russo (Analytical Cellular Pathology)
RNA relocation and the incidence of nucleolus‐like bodies accumulated during mitosis were studied cytochemically in benzo[a]pyrene (BP)‐transformed human breast epithelial MCF‐10F cells after microcell‐mediated transfer of normal chromosomes 11 and 17. The changes resulting from the transfer of these two chromosomes in tumorigenic MCF‐10F cells (BP1‐E cell line) were examined, since alterations in these chromosomes are involved in the expression of the transformed and tumorigenic phenotypes in the MCF‐10F cell series. In addition, the frequency of nucleolus‐like bodies decreases drastically with transformation and tumorigenicity in MCF‐10F cells, thus being conceivable that it would be affected in presence of normal chromosomes 11 or 17. The pattern of RNA relocation associated with the mitotic spindle did not vary in the cell lines analyzed. The introduction of chromosome 17 in BP1‐E cells either decreased or did not affect the frequency of persistent nucleolus‐like bodies. In contrast, in cells which received a normal chromosome 11, the frequency of nucleolus‐like bodies was closer to that of non‐transformed MCF‐10F cells. These results suggest that a normal chromosome 11 but not chromosome 17 contributes to the maintenance of an RNA surplus which accumulates in nucleolus‐like bodies during cell division of the human breast epithelial cells, at least in vitro. Some loci which were retained in the BP1‐E cells which received a normal chromosome 11 are probably involved with the control of RNA transcript production.